2022
DOI: 10.1155/2022/5331474
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I Cutoff for Non-ST-Segment Elevation Myocardial Infarction in Sepsis

Abstract: The diagnostic value and optimal cutoff level of cardiac troponin I in patients with sepsis have not been studied. In this single hospital retrospective study, we assessed the optimal cutoff value of troponin I for diagnosing non-ST-segment elevation myocardial infarction (NSTEMI) with type 1 myocardial infarction (MI) in patients with sepsis who had undergone a percutaneous coronary intervention from 2009 to 2019. In total, 5,341 patients (excluding patients with chronic kidney disease) were included, of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A study on more than 5,000 patients demonstrated that in the presence of sepsis, the optimal cut-off of cTnI for non-STEMI diagnosis was 300 ng/L, and cTn levels were significantly correlated with GRACE scores, with comparable predictive power for 6-month mortality. 44 In patients with kidney disease, the utility of hs-Tn for the diagnosis of AMI is altered by the constant increase in the serum levels of cardiac Tn. In the High-STEACS study, the implementation of hs-Tn testing in the management of patients with kidney disease increased the diagnosis of AMI from 12.4% to 17.8%.…”
Section: Cardiac Troponin and Comorbiditiesmentioning
confidence: 99%
“…A study on more than 5,000 patients demonstrated that in the presence of sepsis, the optimal cut-off of cTnI for non-STEMI diagnosis was 300 ng/L, and cTn levels were significantly correlated with GRACE scores, with comparable predictive power for 6-month mortality. 44 In patients with kidney disease, the utility of hs-Tn for the diagnosis of AMI is altered by the constant increase in the serum levels of cardiac Tn. In the High-STEACS study, the implementation of hs-Tn testing in the management of patients with kidney disease increased the diagnosis of AMI from 12.4% to 17.8%.…”
Section: Cardiac Troponin and Comorbiditiesmentioning
confidence: 99%